(untitled) (diségno, 2019)
The following reflections refer to a few studies on the urban form of Turin whose research methodology was based on the identification of a hierarchy of values characterizing the investigated reality and on the definition of a graphic language suitable for the representation/communication of the results achieved. (read more)